THE FEATURES OF INDIAN DIASPORA AND THEIR IDENTITY IN JUMPHA LAHIRI'S SHORT STORY "UNACCUSTOMED EARTH" - Sugiarto, Tri (Diksi, 2020)
(Title: The Features of Indian Diaspora and Their Identity in Jumpha Lahiri's Short Story "Unaccustomed Earth"). America is a multicultural country. It results from the immigration of various ethnic backgrounds from Asia, Africa, and Europe since the beginning of the 19th century. As one of the ethnic communities in the US, the Indian diaspora encounters many experiences in their life. This article explores the feature and identity of Indian diaspora represented in Lahiri's "Unaccustomed Earth". It aims to reveal some of the Indian diaspora's features in the US and concludes their current cultural identity through analytical reading of the short story. This is a qualitative content analysis. It applies a theory of diaspora to dig the underlying information from the data. The study shows that Indian diaspora experience several features that include having trouble at their first interaction in the country, recalling the tradition of the homeland, associating with the people from the same ethnic background, and processing the idea of going home to the homeland. In the short story, it is found that the characters embody a hybrid identity. Keywords: Indian, diaspora, identity, hybrid, America